Sistem Pengendalian Manajemen, Inovasi, dan Kinerja Organisasi: Tinjauan Literatur Sistematis - Shabrina Dea Sasmaya (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
This study aims to conduct a systematic literature review on the development of management control systems (MCS) and their relationship with innovation, business strategy, and organizational performance. Through an analysis of 20 journal articles published between 1997-2024, the study identified four main themes: (1) the conceptual evolution of MCS from a traditional perspective to a Levers of Control framework; (2) the role of MCS in encouraging organizational innovation; (3) the fit between MCS and business strategy for performance; and (4) MCS transformation in the era of digitalization and crisis. The findings show that MCS not only serves as a control tool but also as an enabler of innovation when designed with a balanced approach. This research identifies research gaps in the context of family companies in Indonesia, the implementation of MCS in conditions of extreme uncertainty, and the role of digitalization in MCS transformation for sustainability. The results of this review provide theoretical contributions in understanding the dynamics of MCS and practical recommendations for managers in designing control systems that support innovation and sustainable performance.